Urgensi al-Wujûh wa al-Nazhâ’ir dalam Alquran - Ahmad, Syukraini (Madania: Jurnal Kajian Keislaman, 2014)
al-Wujûh and an-Nazā`ir are material discussion related to thecontext meaning of vocabulary which are covered in the Qur’an. Al-Wujûh is a word has same form of lafaz butdifferent meaning. Besides, al-Nazhâ’ir has different word but it has same meaning although it contains differentemphasis or impression. Some of moslem scholars have observed and discussed about al-Wujûh and an-Nazā`irand they resulted some formula such as “all words in the Qur’an mean this exepct that one” or “all these wordsin the Qur’an mean this one, except that verse” or “ there is word that means this one in the Qur’ran, except inthis verse”, but the third form is rarely used. Ino rder to produce a correct and accurate rule it needs observation